Efficacy of Amantadine in Improving Cognitive Dysfunction in Adults with Severe Traumatic Brain Injury in Indian Population: A Pilot Study - Ghate, Prajakta Suresh (Asian J Neurosurg, 2018)
BACKGROUND: Severe traumatic brain injury (TBI) is associated with disabling cognitive impairment. Currently available options to improve the cognitive function have been futile. However, recently, commonly used medicine for Parkinson's disease, amantadine, has been shown to assist in the improvement of cognitive function. METHODOLOGY: We conducted a single institution-based observational study in adult Indian population. Fifty consecutive patients with documented static or declining cognitive function at 2 months of severe TBI fulfilling the inclusion/exclusion criteria received amantadine 200 mg/day (100 mg twice a day) orally or through enteral feeding tube for the duration of 4 weeks. The functional assessment done with Full Outline of Unresponsiveness (FOUR) score, Disability Rating Scale (DRS), and Glasgow Outcome Scale (GOS) during 4 weeks of treatment and 2 weeks posttreatment was assessed. RESULTS: The cognitive function improved progressively during the 4-week treatment interval as shown by significant improvement on FOUR score, DRS, and GOS. However, after discontinuation of the drug, the speed of recovery slowed down significantly, but the achieved recovery was not lost. Out of fifty, eight patients had convulsions as an adverse effect of amantadine, of which five patients required discontinuation of the drug with treatment for convulsions. CONCLUSIONS: This study indicates the safety and efficacy of amantadine in partial reversal of cognitive dysfunction in adults with severe TBI in adult Indian population.